Reconstruction of a Major Facial Defect with Multiple Z-Plasty Dermatologic Surgery Article - Batista, Mariana (2020)
Z-plasty is a surgical technique classically used to correct scars. It consists of a double transposition of two or more adjacent triangular-shaped flaps resulting in a Z-shaped scar. This procedure is especially advantageous when the surgical incision is not parallel to the skin tension lines as it allows repositioning of the tension vectors, tending to a more favorable cosmetic result and preventing scar retractions. We present the case of a young woman with a left supraciliary basal cell carcinoma whose excision resulted in an extensive surgical defect which was reconstructed using a multiple Z-patch. The authors describe the surgical technique as well as its main advantages and applicability.